2014
DOI: 10.2478/popore-2014-0029
|View full text |Cite
|
Sign up to set email alerts
|

Cold stress effects on organelle ultrastructure in polar Caryophyllaceae species

Abstract: This study investigated leaf mesophyll cells of Caryophyllaceae plants growing in polar regions -Cerastium alpinum and Silene involucrata from the Hornsund region of Spitsbergen island (Svalbard Archipelago, Arctic), and Colobanthus quitensis from the Ad− miralty Bay region on King George Island (South Shetland Islands, West Antarctic). Ultra− structural changes were analyzed in mesophyll protoplasts of plants growing in natural Arctic and Antarctic habitats and plants grown in a greenhouse, including plants e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
0
9
0
1
Order By: Relevance
“…Although the chloroplast ultrastructure has been characterized in several high‐elevation and polar plants, few studies on warm and continental desert plants have been reported to date. Among plastidic ultrastructures, the presence of ‘chloroplast protrusions’ (broad thylakoid‐free stromal prolongations of chloroplasts, occurring mostly on the latitudinal ends of chloroplasts; Figure ; Holzinger et al , ) have been reported in a broad range of taxa, including polar and alpine species (Giełwanowska et al , , , ; Holzinger et al , ; Lütz et al , ). Cold stress has been widely related to the induction of chloroplast protrusions (Lütz, ; Lütz et al , ), although other stressors such as salinity and nutrient deficiency can also trigger the appearance of protrusions in model plants (Vismans et al , ).…”
Section: Photobiochemistrymentioning
confidence: 99%
“…Although the chloroplast ultrastructure has been characterized in several high‐elevation and polar plants, few studies on warm and continental desert plants have been reported to date. Among plastidic ultrastructures, the presence of ‘chloroplast protrusions’ (broad thylakoid‐free stromal prolongations of chloroplasts, occurring mostly on the latitudinal ends of chloroplasts; Figure ; Holzinger et al , ) have been reported in a broad range of taxa, including polar and alpine species (Giełwanowska et al , , , ; Holzinger et al , ; Lütz et al , ). Cold stress has been widely related to the induction of chloroplast protrusions (Lütz, ; Lütz et al , ), although other stressors such as salinity and nutrient deficiency can also trigger the appearance of protrusions in model plants (Vismans et al , ).…”
Section: Photobiochemistrymentioning
confidence: 99%
“…Colobanthus quitensis is a species of special concern as the only representative of Dicotyledoneae in the maritime Antarctic ( Skottsberg, 1954 ). Colobanthus quitensis has been extensively studied to explore the morphological, physiological and biochemical features that constitute the basis of adaptation to extreme Antarctic conditions ( Bravo et al, 2007 ; Giełwanowska et al, 2011 ; Giełwanowska et al, 2014 ; Bascunan-Godoy et al, 2012 ; Navarrete-Gallegos et al, 2012 ; Pastorczyk, Giełwanowska & Lahuta, 2014 ; Cuba-Díaz et al, 2017 ). In contrast, very little is known about the genetic diversity of this species and the genus Colobanthus ( Androsiuk et al, 2015 ; Koc et al., in press ).…”
Section: Introductionmentioning
confidence: 99%
“…The key factors that inhibit the growth and development of flowering plants in polar regions are low temperature, low water availability and nutrient-poor soil (Billings 1987;Alberdi et al 2002;Block et al 2009). Other environmental hazards include high and largely unpredictable variability in temperature and moisture levels in local habitats (Bliss and Gold 1999;Jónsdóttir 2005;Convey 2012;Chwedorzewska et al 2014;Giełwanowska et al 2014.…”
Section: Discussionmentioning
confidence: 99%